Significant Marketing Strategy in Achieving Enterprise Efficiency (Journal of Universal Excellence, 2026)
Research question (RQ): What is the importance of strategic marketing orientation in achieving organizational efficiency for agile competing companies?Purpose: The purpose of this paper is to explore the importance of marketing strategy in achieving the best possible company efficiency and to systematize some of the most important concepts of marketing strategies in the reference scientific literature.Method: Qualitative research was conducted, previously performed empirical research was used. It is based on an open inductive research methodology; a historical overview was used. Secondary data were collected by reviewing relevant scientific databases, coding and categorization were performed, findings were the basis for analysis, comparison and synthesis of the researched domain, which results in systematization of concepts, processes and individual elements of marketing strategy and its impact on organizational efficiency organizations.Results: The marketing strategy, which derives from the organizational culture and is implemented through the implementation of business policies, focuses on the consumer, for whom the product is designed by adapting marketing elements, is a strategic marketing direction implemented by the company's management structure. Consistent and systematic application of the concept of marketing strategy has a positive effect on organizational efficiency, which results in the creation of agile and competitive companies. The results of organizational efficiency are reflected in favourable financial and market indicators and have a favourable effect on internal organizational efficiency and on the elements of sustainability of society in general.Organization: An organizational management model is defined based on the premise of marketing strategy and focuses on the implementation of such business models, which are based on the internalization of marketing strategy and have a positive impact on organizational efficiency and overall business results of the organization.Society: The final effects of the implementation of the marketing strategy not only have a beneficial effect on the business performance of the organization or its internal efficiency, but can also have a beneficial effect on the wider community by promoting elements of sustainability in society.Originality: A marketing strategy model for agile and competitive companies is proposed, which enables the development of business excellence and efficiency.Limitations / further research: The research is based on empirical findings of selected authors in the field of marketing orientation and marketing strategies, empirical verification of the presented theoretical model is recommended.
Keywords: marketing strategy; business policy; organizational culture; organizational efficiency; agile competing companies